Revisiting Salt Iodization Standards in Nepal: Opportunity and Challenge (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
Iodine deficiency disorder is still a major global public health issue, especially in areas with limited access to iodine-rich food sources. Nepal, a landlocked country in South Asia, has made significant progress in alleviating iodine deficiency disorders by implementing salt iodization initiatives. Maintaining continued success in the elimination of iodine deficiency disorders, it is necessary to revaluate current iodization requirements as the country develops. This paper examines Nepal's present situation with regard to salt iodization, emphasizing the opportunities and challenges of reviewing salt iodization standards.